Pemanfaatan CapCut Untuk Meningkatkan Semangat Belajar dan Kreativitas Siswa IPS Kelas VII H SMPN 1 Mejobo - Elya Aminatul Ulfa; Rimayatun Naja; Silmi Zahra Salsabila; Dany Miftah M Nur (Publikasi Inspirasi Indonesia, 2024)
This research aims to determine the use of the Capcut application as a learning medium to increase students' enthusiasm for learning and creativity in social sciences subjects in class VII H Public Middle School 1 Mejobo Kudus. The method used in this research uses descriptive qualitative research methods, namely to describe the use of the application capcut as a means to increase students' enthusiasm for learning and creativity in social studies subjects. This descriptive research method is research whose data only explains variables one by one. This descriptive research uses a qualitative approach. A qualitative approach is research where the data is in the form of a description. Data collection in this research was carried out in three ways, namely literature study, observation and interviews. The research results showed that students were more enthusiastic about learning in class and increased student creativity by being given the task of making videos using the Capcut application. Apart from that, students can also present the results of the assignments given with enthusiasm. The application of learning media in the form of the CapCut application in social studies learning has proven to be effective in fostering students' enthusiasm for learning and creativity, where they appear active in the teaching and learning process in class. It is hoped that this research can contribute to a more creative and enjoyable use of learning media.